Best Practices for Microbiome Study Design in Companion Animal Research - Jarett, Jessica K.; Kingsbury, Dawn D.; Dahlhausen, Katherine E.; Ganz, Holly H. (Frontiers in Veterinary Science, 2021)
The gut microbiome, the community of microorganisms that inhabit an animal host’s gastrointestinal tract, has important effects on animal health and is shaped by multiple environmental, dietary, and host-associated factors. Clinical and dietary trials in companion animals are increasingly including assessment of the microbiome, but interpretation of these results is often hampered by suboptimal choices in study design. Here, we review best practices for conducting feeding trials or clinical trials that intend to study the effects of an intervention on the microbiome. Choices for experimental design, including a review of basic designs, controls, and comparison groups, are discussed in the context of special considerations necessary for microbiome studies. Diet is one of the strongest influences on the composition of gut microbiomes, so applications specific to nutritional interventions are discussed in detail. Lastly, we provide specific advice for successful recruitment of colony animals and household pets into an intervention study. This review is intended to serve as a resource to academic and industry researchers, clinicians, and veterinarians alike, for studies that test many different types of interventions.